Professional Windows PowerShell - Watt, Andrew, 1953- (Wrox professional guides., 2007)
MSH is a new command-line shell for Microsoft server products, including the long-awaited Longhorn server, and will eventually ship with all major Microsoft products, making it the must-know technology.; MSH will replace current command lines in new Microsoft products and can be used to write shell scripts similar to those used with Unix and Linux.; Discusses how MSH enables all of the.